(untitled) - Brochert, Adam (Philadelphia, PA, 2002)
(Hanley & Belfus) Medical College of Georgia, Savannah. Presents 50 case scenarios to give the reader clear advantage on the vignette-based Step 2 exam. Buzzwords are highlighted, and 'More High-Yield Facts' are included. Softcover.
Keywords: Internal medicine; Computer network resources